2007
DOI: 10.7863/jum.2007.26.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Appearance of the Normal Appendix in Adults

Abstract: The results show that the normal adult appendix can be revealed by sonographic visualization in a large series of asymptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…It seems that many factors, including race, are involved in determining the position of the appendix. Our findings were similar to studies of Denjalić et al [7] and Golalipour et al, conducted in Iran [15], who have evaluated the patients in surgery ward, study of Yabunaka et al [16] who have evaluated the size of appendix by sonography, and study of Ahmed et al [17] who have estimated the appendix size during therapeutic laparotomy. The most common position of appendix has been pelvic position in all of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…It seems that many factors, including race, are involved in determining the position of the appendix. Our findings were similar to studies of Denjalić et al [7] and Golalipour et al, conducted in Iran [15], who have evaluated the patients in surgery ward, study of Yabunaka et al [16] who have evaluated the size of appendix by sonography, and study of Ahmed et al [17] who have estimated the appendix size during therapeutic laparotomy. The most common position of appendix has been pelvic position in all of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…The area located between the psoas muscle and the abdominal wall was the most depicted location for the normal appendix (75%). In contrast, the retrocecal region was the least frequent location for the depiction of the normal appendix [24].…”
Section: Discussionmentioning
confidence: 97%
“…According to other study, the retrocecal appendix is the most common position [ 27]. While in another study the least frequent location is the retrocecal position [24]. Retrocecal localisation is a position where the appendix is difficult to detect by US, which cautions against the method we used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, therefore, changes associated with abdominal pain may facilitate visualization of the appendix. Wiersma et al [30] found that in pediatric subjects, a normal appendix was depicted more frequently than in adults, possibly because there is less attenuation of the ultrasonic beam by subcutaneous fat and muscle, which are thinner in pediatric subjects [31].…”
Section: Discussionmentioning
confidence: 99%